Utilization of Base64 Encryption Repetition for QR Code Presence on Online Attendance - Putra, Iqbal Pratama; Witriyono, Harry; Rifqo, Muhammad Husni; Muntahanah, Muntahanah (Jurnal Komputer, Informasi dan Teknologi, 2022)
The implementation of the attendance system at the University of Muhammadiyah Bengkulu needs to be developed to be more effective in its implementation. This study aims to build a more effective attendance system to answer the problems that still exist in lecture attendance. In the construction of the presence system, the use of base64 encryption repetition is used for the presence of the Qr code. QR Code is used for security and reliability in code scrambling. The randomization was intended to limit students so that they could not make attendance if the class did not match. This is done to ensure that the student is present in class and the lecturer can anticipate student fraud in taking attendance. Therefore, in order to maintain security and avoid leakage and fraud in attendance, we need a system that can protect and maintain the security of a system. Base64 encryption repetition can be used to protect each student's string.